A quantitative perspective to the study of brain arterial remodeling of donors with and without HIV in the Brain Arterial Remodeling Study (BARS) - Gutierrez, Jose; Rosoklija, Gorazd; Murray, Jacinta; Chon, Christina; Elkind, Mitchell S.; Goldman, James E.; Honig, Lawrence; Dwork, Andrew J.; Morgello, Susan; Marshall, Randolph S. (Frontiers in Physiology, 2014)
Mechanisms underlying brain arterial remodeling are uncertain. We tested the hypothesis that arterial size and location are important determinants of arterial characteristics. We collected large and penetrating brain arteries from cadavers with and without HIV. Morphometric characterization was obtained from digital images using color-based thresholding. The association of arterial size and location with lumen diameter, media and adventitia area, media proportion, wall thickness, wall-to-lumen ratio and stenosis was obtained with multilevel mixed models P ≤ 0.05 considered significant. We included 336 brains, in which 2,279 large arteries and 1,488 penetrating arteries were identified. We found that arterial size was significantly associated with all arterial characteristics studied of large and penetrating arteries with exception of arterial stenosis in large arteries. After adjusting for size, an independent association was found between lumen diameters, media and adventitia thickness with artery locations. Arterial stenosis was also associated with artery location in both, large and penetrating arteries. In summary, significant effects of size and/or location were found in arterial characteristics typically used to define arterial remodeling. Brain arterial remodeling characteristics differ across arterial sizes and location, and these differences should be controlled for in future studies of brain arterial remodeling.